PICTURES, LANGUAJE AND REALITY - Renaud Wilmet (Daimon)
The focus of this paper is the evolution of Ludwig Wittgenstein´s use of the word 'picture' (Bild) throughout his works, from the Tractatus to the Philosophical Investigations. The author´s view is that the study of this evolution helps penetrating into the more general transformation of Wittgenstein´s thought, which has now become a major area of study and puzzlement.